Genome methylation in D. melanogaster is found at specific short motifs and is independent of DNMT2 activity - Takayama, Sachiko; Dhahbi, Joseph; Roberts, Adam; Mao, Guanxiong; Heo, Seok-Jin; Pachter, Lior; Martin, David I.K.; Boffelli, Dario

(untitled) (Genome Research, 2014)
Cytosine methylation in the genome of Drosophila melanogaster has been elusive and controversial: Its location and function have not been established. We have used a novel and highly sensitive genomewide cytosine methylation assay to detect and map genome methylation in stage 5 Drosophila embryos. The methylation we observe with this method is highly localized and strand asymmetrical, limited to regions covering ∼1% of the genome, dynamic in early embryogenesis, and concentrated in specific 5-base sequence motifs that are CA- and CT-rich but depleted of guanine. Gene body methylation is associated with lower expression, and many genes containing methylated regions have developmental or transcriptional functions. The only known DNA methyltransferase in Drosophila is the DNMT2 homolog MT2, but lines deficient for MT2 retain genomic methylation, implying the presence of a novel methyltransferase. The association of methylation with a lower expression of specific developmental genes at stage 5 raises the possibility that it participates in controlling gene expression during the maternal-zygotic transition.